Aerodynamic characteristics of a wing-and-flap configuration in ground effect and yaw. (May 2016) - Roberts, Luke S; Correia, Joao; Finnis, Mark V; Knowles, Kevin
The influence of the yaw angle on a model representative of a monoposto racing car's front wing and nose section operating in close proximity to the ground is discussed. The yawed condition is representative of a car operating in a crosswind or with side-slip while cornering. Because of the need for downforce in corners rather than on a straight, it is standard practice to test a racing car at various orientations of yaw, pitch and roll quasi-statically. Wind tunnel testing with a 50%-scale model at a unit Reynolds number of 1.69 × 10 6 was used to investigate the forces and the surface flow structures. The results were then used to validate simulations with the three-equation k – kL – ω transitional turbulence model to observe the surface pressures and the wake structures. It was found that a change in the surface pressure caused asymmetric loading of the wing, the strengthening or inhibiting of vortices depending on their rotational sense and an overall reduction in both the downforce and the drag of the wing; all these were amplified as the yaw angle was increased or the ground clearance reduced. The fundamental aerodynamic flow features of a racing car's front wing operating at yaw are established.